Hydrogen Embrittlement Susceptibility of Pipeline Steel - Juliawati, Alias; Nur Azhani, Abd Razak (Trans Tech Publications Inc., 2013)
The influence of hydrogen on the fracture morphology and mechanical properties of ASTM A106 Grade A pipeline steel has been studied by tension, bend test and hydrogen charging with combination of variation current density and charging time. The appearance of surface damage and fracture morphology were revealed by using field emission scanning electron microscopy. Under the hydrogen charged, the reduction of strength and ductility of the steel revealed from the ultimate tensile strength value and percent of elongation were observed as the current density increased. While, in bend test, the effect of hydrogen is manifested as a decrease in ultimate strength (maximum load in bend test) and bend ductility (bend angle).